(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The present study was intended to analysis the purpose and utilization of lending facilities provided by micro-finance organizations in Kolhapur district and to examine the utilization of loans by borrowers. The required data was collected from the barrowers of micro finance institutions and was analyzed using spss software. The results shows that most loans and advances are taken from purchasing domestic appliances followed by fulfillment of day to day domestic expenses. Overall results depicts that there is no gender wise and social category wise difference in the purpose of loans taken by the barrowers from microfinance institution in study area .However, occupation wise there is difference in the intensions of loans taken from microfinance institutions.